Self-reported Personality Traits and Informant-Rated Cognition: A 10-Year Prospective Study - Sutin, Angelina R. (J Alzheimers Dis, 2019)
Personality traits, such as higher Neuroticism and lower Conscientiousness, are associated with risk of Alzheimer’s disease and other dementias. A diagnosis of dementia relies, in part, on informant ratings of the individual’s cognitive status. Here we examine whether self-reported personality traits are associated with four measures of informant-rated cognition up to a decade later. Participants from the Health and Retirement Study (N=2,536) completed a five-factor model measure of personality in 2006 or 2008. Informants completed the 2016 Harmonized Cognitive Assessment Protocol (HCAP), which included ratings of the participant’s current cognitive functioning and change in cognitive function over the last decade assessed with the IQCODE, Blessed, 1066, and CSID. Controlling for characteristics of the participant, informant, and their relationship, higher Neuroticism and lower Conscientiousness were associated consistently with worse informant-rated cognition. The association between Openness and better informant-rated cognition was due primarily to higher baseline cognitive function. Extraversion and Agreeableness were associated with better informant-rated cognition only among participants who were cognitively intact at follow-up. The present research suggests that knowledgeable informants are able to detect cognitive deficits associated with personality.